Polystyrene‐Supported Triphenylsilyl Chloride for the Silylation‐Based Kinetic Resolution of Secondary Alcohols. Issue 10 (27th April 2015) - Akhani, Ravish K.; Clark, Robert W.; Yuan, Liang; Wang, Li; Tang, Chuanbing; Wiskur, Sheryl L.
Abstract A silyl chloride derivatized styrene polymer was employed in the silylation‐based kinetic resolution of secondary alcohols for chromatography‐free separation of alcohol enantiomers. Synthetically useful selectivity factors were obtained; furthermore, the polymer was recycled for use in a subsequent kinetic resolution, and it maintained its selectivity and integrity.